2002
DOI: 10.1063/1.1520336
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of electric breakdown during ion bombardment of organic insulators using a cluster ion beam

Abstract: Ion and electron bombardment-related ion emission during the analysis of diamond using secondary ion mass spectrometry

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
12
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…This was discovered early on by Appelhans and Delmore (1987) and has been confirmed several times since in both organic and polymeric samples (Hirata et al, 2002(Hirata et al, , 2003. With C þ 60 , charge compensation is often not required, even in the dynamic SIMS mode (Xu et al, 2004;Cheng & Winograd, 2005).…”
Section: B Decreased Chargingmentioning
confidence: 79%
See 1 more Smart Citation
“…This was discovered early on by Appelhans and Delmore (1987) and has been confirmed several times since in both organic and polymeric samples (Hirata et al, 2002(Hirata et al, , 2003. With C þ 60 , charge compensation is often not required, even in the dynamic SIMS mode (Xu et al, 2004;Cheng & Winograd, 2005).…”
Section: B Decreased Chargingmentioning
confidence: 79%
“…It has been repeatedly shown that employing cluster sources can eliminate charging (Appelhans & Delmore, 1987;Hirata et al, 2002Hirata et al, , 2003Xu et al, 2004;Cheng & Winograd, 2005). This was discovered early on by Appelhans and Delmore (1987) and has been confirmed several times since in both organic and polymeric samples (Hirata et al, 2002(Hirata et al, , 2003.…”
Section: B Decreased Chargingmentioning
confidence: 82%
“…Cluster ion impact on a target produces different secondary ion emission yields compared with those for monoatomic ions because of the unique irradiation phenomenon that the constituent atoms of an incident cluster simultaneously impact on a very small region of the target surface [1][2][3][4][5]. As higher emission yields of secondary ions useful for surface analysis have been observed for various combinations of cluster ions and targets, several attempts have been made to apply cluster ion beams to primary ions for secondary ion mass spectroscopy [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…6,7 Cluster ion bombardment provides nonlinear irradiation effects on secondary emissions, [8][9][10] which lead to a charge accumulation process that differs from the process for monoatomic ions. 11 In our previous work, we compared monoatomic ion C 1 ϩ versus cluster ion C 8 ϩ bombardments on the charge accumulation processes of an organic insulator by simultaneously measuring the target and secondary emission currents as functions of atomic dose. 11 We found that the electric breakdown caused by charge accumulation during the ion bombardment can be avoided by using cluster ions instead of monoatomic ions.…”
mentioning
confidence: 99%
“…11 In our previous work, we compared monoatomic ion C 1 ϩ versus cluster ion C 8 ϩ bombardments on the charge accumulation processes of an organic insulator by simultaneously measuring the target and secondary emission currents as functions of atomic dose. 11 We found that the electric breakdown caused by charge accumulation during the ion bombardment can be avoided by using cluster ions instead of monoatomic ions. 11 This advantage of cluster ions arises from a lower absolute charging potential that stems from charged secondary emission phenomena occurring in cluster ion impact.…”
mentioning
confidence: 99%